Respostas
respondido por:
0
an = 840
a1 = 10
a2 = 12
r = a2 - a1
r = 12 - 10
r = 2
an = a1 + (n - 1).r
840 = 10 + (n - 1).2
840 - 10 = 2n - 2
830 = 2n - 2
830 + 2 = 2n
832 = 2n
2n = 832
n = 832/2
n = 416
R.: 416 termos.
a1 = 10
a2 = 12
r = a2 - a1
r = 12 - 10
r = 2
an = a1 + (n - 1).r
840 = 10 + (n - 1).2
840 - 10 = 2n - 2
830 = 2n - 2
830 + 2 = 2n
832 = 2n
2n = 832
n = 832/2
n = 416
R.: 416 termos.
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás